Molybdenum and hydrogen sulfide synergistically mitigate arsenic toxicity by modulating defense system, nitrogen and cysteine assimilation in faba bean (Vicia faba L.) seedlings. (1st December 2021) - Siddiqui, Manzer H.; Alamri, Saud; Mukherjee, Soumya; Al-Amri, Abdullah A.; Alsubaie, Qasi D.; Al-Munqedhi, Bander M.A.; Ali, Hayssam M.; Kalaji, Hazem M.; Fahad, Shah; Rajput, Vishnu D.; Narayan, Om Prakash
Abstract: Hydrogen sulfide (H2 S) has emerged as a potential gasotransmitter in plants with a beneficial role in stress amelioration. Despite the various known functions of H2 S in plants, not much information is available to explain the associative role of molybdenum (Mo) and hydrogen sulfide ( H2 S) signaling in plants under arsenic toxicity. In view to address such lacunae in our understanding of the integrative roles of these biomolecules, the present work attempts to decipher the roles of Mo and H2 S in mitigation of arsenate (AsV) toxicity in faba bean ( Vicia faba L.) seedlings. AsV-stressed seedlings supplemented with exogenous Mo and/or NaHS treatments (H2 S donor) showed resilience to AsV toxicity manifested by reduction of apoptosis, reactive oxygen species (ROS) content, down-regulation of NADPH oxidase and GOase activity followed by upregulation of antioxidative enzymes in leaves. Fluorescent localization of ROS in roots reveals changes in its intensity and spatial distribution in response to MO and NaHS supplementation during AsV stress. Under AsV toxicity conditions, seedlings subjected to Mo + NaHS showed an increased rate of nitrogen metabolism evident by elevation in nitrate reductase, nitrite reductase and glutamine synthetase activity. Furthermore, the application of Mo and NaHS in combination positively upregulates cysteine and hydrogen sulfide biosynthesis in the absence and presence of AsV stress. Mo plus NaHS-supplemented seedlings exposed to AsV toxicity showed a substantial reduction in oxidative stress manifested by reduced ELKG, lowered MDA content and higher accumulation of proline in leaves. Taken together, the present findings provide substantial evidence on the synergetic role of Mo and H2 S in mitigating AsV stress in faba bean seedlings. Thus, the application of Mo and NaHS reveals their agronomic importance to encounter heavy metal stress for management of various food crops. Graphical abstract: Image 1 Highlights: Molybdenum (Mo) and hydrogen sulfide (H2 S) synergistically mitigated arsenic stress. Mo and H2 S efficiently reduced overproduction of reactive oxygen species. Exogenous Mo and H2 S concomitantly regulated antioxidative defense system. Mo and H2 S modulated nitrogen and proline metabolism under arsenic toxicity. Mo and H2 S triggered cysteine and H2 S biosynthesis in seedlings under arsenic stress.